Penerapan Metode Eksplorasi Dalam Meningkatkan Hasil Belajar Matematika Pada Peserta Didik Kelas IX SMP Negeri 5 Campalagian - Suryadi Ishak (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This research is an experimental research which observed the influence of the use of exploratory method in improving mathematics learning outcomes in the students of Class IX of SMP Negeri 5 Campalagian. The sampling technique used in this research is random sampling. Sample determination was done randomly from 3 classes with 99 a population, each class has the same chance of being sampled. IXB class as experimental class taught by using exploration method with 25 students and IXA class as control class taught by using conventional learning, there is 25 people of learn. Each class is taught in the same frequency of meetings and on the same subject. The experimental class uses exploratory method and control class using conventional approach. The results of mathematics learning are obtained on prêt-test and post-test. Thus, in the experimental class obtained prêt-test average score of 56.00 while the post-test of 75.40. In the control class obtained the average score of pre-test of 61.40 while in the post-test of 67.60. Judging from the average result of the students showed a significant difference, seen from the results of hypothesis testing obtained value of 2.136, while for the value of which means that, it can be said that there is a different application of exploratory methods with the application of conventional methods of mathematics learning outcomes in participants Students Class IX SMP Negeri 5 Campalagian.